2017
DOI: 10.1177/0269215517705181
|View full text |Cite
|
Sign up to set email alerts
|

Embedding an enriched environment in an acute stroke unit increases activity in people with stroke: a controlled before–after pilot study

Abstract: Embedding an enriched environment in an acute stroke unit increased activity in stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 37 publications
5
93
0
Order By: Relevance
“…The programme was well-tolerated by participants, and more than 90% reported satisfaction. The overall beneficial effects of EE in this study are consistent with previous studies of EE programmes (15,26,36,37). In our previous RCT (26), we reported favourable impact of the "Activity Hub" on functional and cognitive functions (such as depression, anxiety, stress); coping and self-management skills in an inpatient neurological cohort.…”
Section: Discussionsupporting
confidence: 91%
“…The programme was well-tolerated by participants, and more than 90% reported satisfaction. The overall beneficial effects of EE in this study are consistent with previous studies of EE programmes (15,26,36,37). In our previous RCT (26), we reported favourable impact of the "Activity Hub" on functional and cognitive functions (such as depression, anxiety, stress); coping and self-management skills in an inpatient neurological cohort.…”
Section: Discussionsupporting
confidence: 91%
“…Numerous behavioural mapping studies have reported that patients engage in little physical activity on stroke units [e.g. 30,31]. In the present study, stroke survivors reported an increase in standing and moving once they returned home.…”
Section: Levels and Patterns Of Sedentary Behaviour After Strokesupporting
confidence: 46%
“…Although the importance of task specificity in optimizing rehabilitation has been acknowledged for more than a decade, 13,53 general acceptance that environmental enrichment provides robust sensorimotor benefits that may be applicable to clinical rehabilitation has only recently begun to emerge. 25,47 Promising, new clinical studies in stroke rehabilitation are using environmental enrichment principles, resulting in increased patient activity 54 and decreased time spent inactive and alone. 55 Further clinical application of environmental enrichment in conjunction with task-specific training to increase rehabilitation intensity may result in a cost-effective method of improving function and quality of life for stroke survivors.…”
Section: Strokementioning
confidence: 99%